The black stallion [videorecording (DVD)] - Reno, Kelly, 1966-; Garr, Teri, 1944-2024; Rooney, Mickey; Muse, Clarence; Farley, Walter, 1915-1989 (MGM Home Entertainment, 2009)
Boy and horse are shipwrecked on an island where they become fast friends. Upon their return home they work together for a try in one of the great races at Santa Anita.